Russia’s Political Steps in the “Armenian Question” And the Pact On 26 January, (8 February) 1914 Between Russia and Turkey (Zien Journal of Social Sciences and Humanities, 2021)
The main aim of this paper is to research the role of Tsar Russia in spreading of Armenian question which being artificial policy. It should be noted that Tsar Russia had played important role political revive in the community of Armenian living in the Ottoman Empire. Additionally, it is studied Great Power’s economic and political policy in the Armenian question. Towards the latter part of the nineteenth century the decline of the Ottoman Empire became acute. The expansionist Powers, taking advantage of this decline, waited impatiently to share the carcass of dying “Sick Man of Europe”. In order to hasten his demise, they encouraged the growing nationalist movements in that empire, particularly in the Balkans. As a result there were rebellions in Herzegovina and Bulgaria in the 1870s, with the covert or overt assistance of some of these Powers, who vied with one another for the control of the Near and Middle East, in general, of the Balkans, Istanbul and Straits, and later (through the Armenians), of the eastern provinces of the Ottoman Empire in particular, in order to satisfy their interests. The only impediment that kept them from delivering the final blow was the possibility that, if the Ottoman Empire did collapse, their rivalries would provoke a conflict of incalculable proportions. However, if that empire had to be maintained, it had to be kept weak; for a powerful empire might destroy the fabric of interests, commercial and otherwise, that the Powers wove out of the decline of the Ottoman State.